Cabergoline Preserves Implantation and Ongoing Pregnancy Rates in High Responders to Gonadotropin [22P]. (May 2017) - Wilson, Alexandra; Shu, Yimin; Patel, Bansari; Berga, Sarah; Prokai, David; Johnston-MacAnanny, Erika
Abstract : INTRODUCTION: While infrequent, excessive response to gonadotropin occurs in spite of careful pre-cycle planning. We sought to determine the impact of cabergoline administration on implantation, clinical and ongoing pregnancy rates in patients with excessive response to gonadotropins without other features of ovarian hyperstimulation syndrome (OHSS) during fresh embryo transfer. METHODS: All fresh IVF cycles undergoing embryo transfer from 2013-2016 in an academic center were reviewed to identify cycles with excessive response to gonadotropin. Patients were excluded if their embryos underwent preimplantation genetic screening or if early OHSS was diagnosed necessitating cryopreservation. All patients were triggered with urinary hCG and oocyte collection occurred 36 hours after trigger. Administration of cabergoline at the time of hCG trigger stratified the two groups. Choice to administer cabergoline was based on provider discretion. Differences between groups were obtained through chi-squared analysis. RESULTS: Sixteen patients (N=16) met inclusion criteria for study. Subjects were equally divided into cabergoline exposure (N=8) and absence of cabergoline exposure (N=8). The implantation rates were 28.5% (4/14) and 63.3% (7/11), in the non-exposure and exposure groups respectively. 50% (4/8) of the non-exposure group versus 75% (6/8) exposure group achieved clinical pregnancy. Ongoing pregnancy rates were identical with 75% rate (6/8) in both groups. CONCLUSION: In high responders, those who had co-administration of cabergoline maintain outstanding implantation rates and clinical and ongoing pregnancy rates. In patients exposed to cabergoline without other features of OHSS, embryo transfer may be carefully considered without compromise of implantation rates, particularly in those with high response.